Hermanos, estorvos, ameaças: identidade e tensividade na representação de estrangeiros latino-americanos pelo portal G1 - Maia, Luana Ingrid Gomes (2024)
Every year, Brazil receives an impressive quantity of foreigners. Over the last decade, this contingent has begun to be made up mainly of citizens of other Latin American nations, who prevail regarding both immigration and tourism (CAVALCANTI; OLIVEIRA; SILVA, 2021; MINISTÉRIO DO TURISMO, 2022). Considering, therefore, that these individuals are strongly inserted in the Brazilian quotidian, this paper aims to verify how the national press – which, owing to its reach and persuasion power, is one of the most relevant creators and broadcasters of cultural stereotypes – shapes the identity construction of this group. In this work, focus falls upon headlines and subheadlines published on the principal Brazilian news website, G1 (REUTERS INSTITUTE, 2022), in order to reach three objectives. The first one is to check to what extent there is an isotopy that is common to all analyzed nationalities and that results in an image-end of this collective. The second one, in its turn, is to identify which factors influence the tensive dynamics built by G1 when announcing facts involving this group. Finally, the third one is to detect which alterity regime is mainly employed regarding Latin-American foreigners and how it is validated by the meaning effects that result from the tensive modulations implemented in the discursive domain. In order to achieve these goals, this work employed the theoretical framework of Tensive Semiotics (FONTANILLE, 2001 [1998]; FONTANILLE; ZILBERBERG, 2016 [1998]; ZILBERBERG, 2016a [2012]; ZILBERBERG, 2016b [2006]), with an emphasis on the extensive operations of sorting and mixture. Likewise, elements concerning the generative trajectory of meaning were applied (BARROS, 1997; FIORIN, 2000; BERTRAND, 2003) – especially the components of the discursive level –, in addition to the developments of Sociosemiotics (LANDOWSKI, 2012), mainly in what corresponds to identity dynamics in contexts of social interaction and contact with otherness. Subsequently, these concepts were used to qualitatively analyze a corpus of 40 texts, which alluded to local events involving Argentines, Bolivians, Colombians, Paraguayans, and Venezuelans. At the end of the analysis, it was found that the identity construction operated by G1 is anchored in social stereotypes and constitutes a /make believe/ that conceives such foreigners fundamentally as criminals or helpless, which establishes a derogatory representation of the mentioned nationalities. Furthermore, G1 employs intelligibility to segregate these citizens, sorting them mainly according to the isotopies that are realized and actualized in the discourse. Consequently, the unfavorable manner in which these individuals are represented appears as a manifest and incontestable fact, which stimulates a subtle aversion against that collectivity.